Effects of Abscisic Acid on the Hydraulic Conductance of and the Total Ion Transport through Phaseolus Root Systems - Fiscus, Edwin L. (1981)
The response of solute and volume fluxes of Phaseolus root systems to applied AbA was observed under conditions of applied pressure which were used to enhance the volume flow. The growth regulator elicited three separate responses: a transient release of solutes to the xylem which was responsible for an initial increase in volume flux; a long term increase in the total ion flux; and a long term decrease in the hydraulic conductance of the root systems. The exact response was highly dependent on the magnitude of the pre-AbA volume flux density, the relative contributions of osmotic and pressure-induced flow, and the applied dosage. Calculations suggested that the volume flux in naturally exuding root systems is relatively insensitive to changes in the conductance.